Influence of cattle on browsing and grazing wildlife varies with rainfall and presence of megaherbivores - Kimuyu, Duncan M; Veblen, Kari E; Riginos, Corinna; Chira, Robert M; Githaiga, John M; Young, Truman P (Ecological applications, 2017)
In many savanna ecosystems worldwide, livestock share the landscape and its resources with wildlife. The nature of interactions between livestock and wildlife is a subject of considerable interest and speculation, yet little controlled experimental research has been carried out. Since 1995, we have been manipulating the presence and absence of cattle and large mammalian herbivore wildlife in a Kenyan savanna in order to better understand how different herbivore guilds influence habitat use by specific wildlife species. Using dung counts as a relative assay of herbivore use of the different experimental plots, we found that cattle had a range of effects, mostly negative, on common mesoherbivore species, including both grazers and mixed feeders, but did not have significant effects on megaherbivores. The effect of cattle on most of the mesoherbivore species was contingent on both the presence of megaherbivores and rainfall. In the absence of megaherbivores, wild mesoherbivore dung density was 36% lower in plots that they shared with cattle than in plots they used exclusively, whereas in the presence of megaherbivores, wild mesoherbivore dung density was only 9% lower in plots shared with cattle than plots used exclusively. Cattle appeared to have a positive effect on habitat use by zebra (a grazer) and steinbuck (a browser) during wetter periods of the year but a negative effect during drier periods. Plots to which cattle had access had lower grass and forb cover than plots from which they were excluded, while plots to which megaherbivores had access had more grass cover but less forb cover. Grass cover was positively correlated with zebra and oryx dung density while forb cover was positively correlated with eland dung density. Overall these results suggest that interactions between livestock and wildlife are contingent on rainfall and herbivore assemblage and represent a more richly nuanced set of interactions than the longstanding assertion that cattle simply compete with (grazing) wildlife. Specifically, rainfall and megaherbivores seemed to moderate the negative effects of cattle on some mesoherbivore species. Even if cattle tend to reduce wildlife use of the landscape, managing simultaneously for livestock production (at moderate levels) and biodiversity conservation is possible.